2020
DOI: 10.20896/saci.v8i1.795
|View full text |Cite
|
Sign up to set email alerts
|

Role of Literary Pedagogy in Modern Education of Preschool and Primary School Children

Abstract: The study examines the concept of literary pedagogy as an integral part of the educational process. The authors argue that literary pedagogy as a modern trend in human development is linked to the system of continuous education, which is implemented in formal, non-formal and informal education. A distinction should be drawn between the concepts of literary education and literary pedagogy. Literary education as a process of an individual’s incorporation into the culture by means of literature is generally provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is an active skill to construct the meaning of the written text in the target language through relating the written information with students' background knowledge. Reading comprehension is beneficial in promoting students' language learning since it trains them to process and understand the information in the target language (Fathiara et al, 2019;Shastina et al, 2020). Therefore, fostering EFL students' reading comprehension is worth noted in teaching the target language.…”
Section: Introductionmentioning
confidence: 99%
“…It is an active skill to construct the meaning of the written text in the target language through relating the written information with students' background knowledge. Reading comprehension is beneficial in promoting students' language learning since it trains them to process and understand the information in the target language (Fathiara et al, 2019;Shastina et al, 2020). Therefore, fostering EFL students' reading comprehension is worth noted in teaching the target language.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with a simple but complex explanation, it makes it easier for students to absorb information related to economic problems that tend to be varied and different in each region and country. On the other hand, long-term use can improve the pedagogical abilities of prospective economics teachers, most of which require strong analytical skills on economic problems (Hogan & Devi, 2019;Shastina et al, 2020;Han & Zhang, 2021). Based on this, it can be concluded that this digital book can be a real solution in overcoming students' problems in understanding macroeconomic material.…”
Section: Resultsmentioning
confidence: 91%
“…is iterative identification method uses the latest q-group data up to the current moment t for parameter estimation, and when the iteration reaches a certain number of steps (or the parameter estimation accuracy does not improve), it stops the iterative computation and moves the data window forward one step to introduce new observations, while removing the old data inside the data window, keeping the q-group data inside the window, and then using the data in the new window for iterative computation [15]. e data in the new window are then used to iteratively compute the parameter estimates, and the computation continues in this way until the parameter accuracy is achieved.…”
Section: Improved Multivariate Nonlinear Matrix Correlationmentioning
confidence: 99%